Dear Dumb Diary / No. 6, The problem with here is that it's where I'm from : by Jamie Kelly - Benton, Jim (New York : Scholastic, 2004)
Jamie Kelly shares with her diary her excitement about the fact that students from Wodehouse Middle School will be going to Mackerel Middle School temporarily.
"Apple series"--Cover pages [4].
"Jim Benton's tales from Mackerel Middle School."
008-up.
5.
Keywords: Diaries -- Juvenile fiction; Middle school students -- Juvenile fiction; Middle schools -- Juvenile fiction; Diaries -- Fiction; Humorous stories; Middle school students -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Humorous fiction; Diary fiction